The Routledge handbook of teaching English to young learners - Garton, Sue 1961-; Copland, Fiona 1962- (Routledge handbooks in applied linguistics, 2022)
"The Routledge Handbook of Teaching English to Young Learners celebrates the 'coming of age' for the field of research in teaching English to young learners, with 33 chapters written by a range of international scholars including from East Africa, Mexico, South Pacific, Japan, France, the USA and the UK. Taking a thematic and interdisciplinary approach, this volume draws on areas such as second language acquisition, discourse analysis, pedagogy and technology, and provides: - An overview of the current state of the field, identifying key areas of TEYL; - Chapters on broad range of subjects from methodology to teaching in difficult circumstances and from CLIL to gaming; - Suggestions of ways forward, with the aim of shaping the future research agenda of TEYL in multiple international contexts; - Background research and practical advice for students, teachers and researchers. With extensive guidance on further reading throughout, The Routledge Handbook of Teaching English to Young Learners is an essential guide for those studying and researching in this area"...